IT ENTREPRENEURSHIP IN INDEPENDENT UKRAINE: AN ATTEMPT AT A SOCIO-HISTORICAL PERIODIZATION (City: History, Culture, Society, 2026)
Based on an analysis of academic studies, analytical reports, journalistic retrospectives, and regulatory documents, the article proposes a social-historical periodization of the development of IT entrepreneurship in Ukraine from 1991 to the early 2020s. The research is grounded in the approach of social history, which makes it possible to consider IT entrepreneurship not only as an economic or technological activity, but as part of broader social transformations. The focus is placed not merely on quantitative indicators of industry growth, but primarily on changes in the organization of labor, professional practices, forms of interaction, and social perceptions.Within the proposed periodization, five main stages are identified, reflecting the sequential evolution of IT entrepreneurship in Ukraine. These stages encompass the transition from isolated initiatives and the first IT firms of the 1990s, which operated under conditions of institutional uncertainty and limited access to markets, to the formation in the 2010s of a structured industry with established organizational models, a developed community infrastructure, and a growing product segment. The study traces a shift in entrepreneurial logic-from service-oriented models to the emergence of companies that create their own technological products and integrate into global value chains.The analytical focus of the article is concentrated on several interrelated dimensions: the evolution of organizational structures of IT companies, the transformation of professional roles and labor models, the formation of an internal culture of the IT sector, as well as the development of external perceptions of IT professionals as a distinct social group. It is shown that the development of IT entrepreneurship in Ukraine was uneven and largely determined by a combination of global market influences and internal social factors, in particular professional self-organization and horizontal ties within the community.The proposed social-historical periodization does not claim to be definitive; however, it provides an analytical framework for further research on the history of IT entrepreneurship in Ukraine and may be used for in-depth analysis of specific stages, practices, and social transformations associated with the development of the digital economy.
Keywords: IT entrepreneurship; periodization; Ukrainian IT industry; social history; professional community; IT professionals; social perceptions; organizational structures; late socialism